Application of an electrochemical treatment for EDDS soil washing solution regeneration and reuse in a multi-step soil washing process: Case of a Cu contaminated soil. (1st November 2015) - Ferraro, Alberto; van Hullebusch, Eric D.; Huguenot, David; Fabbricino, Massimiliano; Esposito, Giovanni
Abstract: Soil washing is an extensively used process for remediation of heavy metals contaminated soils. However the amount of fresh washing solution to be used represents a significant economical drawback of this process. This paper investigates the application of an electrochemical process (Fe/Fe electrodes couple) for the regeneration of a spent EDDS solution, containing Cu and major competitor cations (Ca, Fe, Mg, and Mn). The effect of current density, pH and conductivity of the washing solution on the recovery process performances was investigated. Current density showed the highest influence on Cu, Mg and Mn removal yields. Maximum removal yields reached 99% for Cu, 77% for Mn and 49% for Mg. No influence of the investigated parameters on Ca removal was observed, while an increase of Fe concentration due to anode dissolution occurred. Characterization of sludge produced from the 2 h electrochemical test (5 mA cm −2, pH = 8, 8 mS cm −1 ) displayed concentrations of 2.8 g kg −1 for Ca, 0.4 g kg −1 for Cu, 535.6 g kg −1 for Fe, 2.6 g kg −1 for Mg. TCLP tests at pH 2.88 and 4.93 showed a low leaching percentage (Ca, 10–21%; Cu, 6–12%; Fe, 0.22% Mg, 27–36%). Multi-washing tests were carried out to assess the decrease of the chelating ability of the regenerated washing solution and the Cu extraction efficiency. Highlights: Process efficiency is mainly dependent on the variation of current density values. Almost complete Cu removal occurs at high values of current density (5–8 mA cm −2 ). Regenerated EDDS solution reusability is observed for 3 washing steps on new soils. Constant removal efficiency decrease occurs for regenerated/fresh EDDS solutions. The highest regenerated EDDS solution efficiency drop occurs after 4 washing steps.